Effect of L-dopa with and without inhibition of extra cerebral dopa decarboxylase on gastric acid secretion and gastrin release in man. Issue 10 (October 1985) - Caldara, R; Barbieri, C; Piepoli, V; Borzio, M; Masci, E
Abstract : The present study was undertaken to investigate the possibility that central nervous system monoaminergic pathways may play a role in the control of gastric acid and gastrin secretion in man. Submaximal pentagastrin stimulated (0.25 micrograms/kg/h) gastric acid secretion, as well as basal gastrin concentrations were studied in two groups of subjects. The first group received oral administration of placebo and the catecholamine precursor L-dopa (500 mg); the second group was treated with placebo and the association of L-dopa (100 mg) plus carbidopa (35 mg) after pretreatment with carbidopa (50 mg every six hours for four doses), a schedule which is known to increase brain catecholamine concentrations. In comparison with placebo, stimulated gastric acid secretion was reduced by L-dopa alone, whereas was not modified by L-dopa plus carbidopa. Basal gastrin concentrations were increased after L-dopa and after L-dopa plus carbidopa. These data show that basal gastrin concentration is raised by central catecholamine augmentation; but gastric acid secretion seems to be influenced by changes of peripheral catecholamine concentrations. It is suggested that dopamine and perhaps noradrenaline, but not adrenaline, are important in these effects.